N-Succinylaspartic-Acid-Conjugated Riluzole Is a Safe and Potent Colon-Targeted Prodrug of Riluzole against DNBS-Induced Rat Colitis - Jaejeong Kim; Changyu Kang; Jin-Wook Yoo; In-Soo Yoon; Yunjin Jung (Pharmaceutics, 2023)
In our previous study, riluzole azo-linked to salicylic acid (RAS) was prepared as a colon-targeted prodrug of riluzole (RLZ) to facilitate the repositioning of RLZ as an anticolitic drug. RAS is more effective against rat colitis than RLZ and sulfasalazine, currently used as an anti-inflammatory bowel disease drug. The aim of this study is to further improve colon specificity, anticolitic potency, and safety of RAS. N-succinylaspart-1-ylRLZ (SAR) and N-succinylglutam-1-ylRLZ (SGR) were synthesized and evaluated as a “me-better” colon-targeted prodrug of RLZ against rat colitis. SAR but not SGR was converted to RLZ in the cecal contents, whereas both conjugates remained intact in the small intestine. When comparing the colon specificity of SAR with that of RAS, the distribution coefficient and cell permeability of SAR were lower than those of RAS. In parallel, oral SAR delivered a greater amount of RLZ to the cecum of rats than oral RAS. In a DNBS-induced rat model of colitis, oral SAR mitigated colonic damage and inflammation and was more potent than oral RAS. Moreover, upon oral administration, SAR had a greater ability to limit the systemic absorption of RLZ than RAS, indicating a reduced risk of systemic side effects of SAR. Taken together, SAR may be a “me-better” colon-targeted prodrug of RLZ to improve the safety and anticolitic potency of RAS, an azo-type colon-targeted prodrug of RLZ.